PROSES REKRUTMEN, SELEKSI DAN PENEMPATAN DALAM MENJAWAB ISU-ISU BARU PENDEKATAN MANAGEMEN SUMBER DAYA MANUSIA - sonia - redmana; shoffan nizomi; taufik hidayat; sujarwati sujarwati (Diversity: Jurnal Ilmiah Pascasarjana, 2021)
Quality human resources are one of the basic assets and keys of the success of a company or organization to achieve its goals. Through good human resource management, it will produce quality human resources so that productivity, performance and employee commitment to the company will increase and produce better products in quality and quantity with the same human resources. One of the most important things in human resource management activities is appropriate Recruitment, Selection and Placement accompanied by HR Development. The research objective in this paper is to determine the process of recruitment, selection and placement of employees to become staff in a medical record installation conducted at a hospital in Kota Bo-Gor. The results of recruitment and selection as well as tests for new employee candidates for medical record formations show that among the seven applicants who entered there were two employees who were accepted and one employee who was accepted with not so high scores but the results of the interviews showed sincerity, commitment and responsibility at work, hospital needs.